EPISTEMOLOGICAL POSTULATES OF AFRICAN INDEGINOUS EDUCATION INHERENT IN THE KENYAN EDUCATION SYSTEM - Shani, Ominde Eliud (IJRDO- Journal of Educational Research, 2017)
The paper examines the concept of knowledge in African indigenous education. TraditionalAfrican education has specific epistemological postulates that are relevant to the Kenyaneducation system. The study also explores some of the shortcomings of African indigenouseducation.